DL

Tìm x : 

3 . { 3 - [ 3 - ( 3 - x ) ] } = 0

LT
19 tháng 8 2016 lúc 15:28

ta có : 3.{3-[3-(3-x)]} =0

          3. [ 3- (3 -3 +x )] =0

          3. ( 3 - x ) =0

           3 - x = 0

           x = 3

  vậy x = 3 

Bình luận (0)
TM
19 tháng 8 2016 lúc 15:30

=> 3-[3-(3-x)]=0

=> 3-(3-x)=3-0=3

=>3-x=3-3

=> 3-x=0

=>x=3-0=3

Bình luận (0)
ND
19 tháng 8 2016 lúc 15:40

3.{ 3 - [ 3 - ( 3 - x ) ] } = 0

3.[ 3 - ( 3 - 3 + x ) ] = 0

3. ( 3 - 3 + 3 - x ) = 0

3 . ( 3 - x ) = 0

9 - 3x = 0

x = 3

Vậy x = 3

Bình luận (0)
H24
19 tháng 8 2016 lúc 16:56

3.{3-[3-(3-x)]}=0

3-[3-(3-x)]=0:3

3-(3-x)=3-0

3-x=3-3

   x=3-0 

   x=3

Bình luận (0)